1968
DOI: 10.1111/j.1365-2133.1968.tb11903.x
|View full text |Cite
|
Sign up to set email alerts
|

X-Ray Emission Microanalysis of the Density of Hair Proteins in Kwashiorkor

Abstract: Hair samples were obtained from the scalps of 5 infants with kwashiorkor and 5 matched control infants on a balanced diet.The greatest diameters of the hairs were measured in their natural state, ethanol, xylol, water and air. The diameters of the kwashiorkor hairs were 8 to 22% larger in water than in air while the diameters of the control hairs were 5 to 8% larger. This indicates that the stability of the cross links between the polypeptide chains of hair proteins is reduced in kwashiorkor.The mass per unit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

1968
1968
1981
1981

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 2 publications
(1 reference statement)
0
7
0
Order By: Relevance
“…Sims (1967Sims ( ,1968 pointed out that a decrease in hair shaft diameter usually preceded the other symptoms of kwashiorkor and that the tensile strength was also lowered. The atrophied bulb, plucked at the end of this period, manifests distal constriction extending for a short distance along the shaft, and these changes are reversible to some extent when protein is added to the diet.…”
Section: The Effect Of Nutrition On Hair Growthmentioning
confidence: 99%
See 1 more Smart Citation
“…Sims (1967Sims ( ,1968 pointed out that a decrease in hair shaft diameter usually preceded the other symptoms of kwashiorkor and that the tensile strength was also lowered. The atrophied bulb, plucked at the end of this period, manifests distal constriction extending for a short distance along the shaft, and these changes are reversible to some extent when protein is added to the diet.…”
Section: The Effect Of Nutrition On Hair Growthmentioning
confidence: 99%
“…The quantitative diameter is considered as an useful index of protein synthesis in the management of cases of malnutrition (Sims 1968). The quantitative diameter is considered as an useful index of protein synthesis in the management of cases of malnutrition (Sims 1968).…”
Section: Comparative Studies Of the Diameters Of Hairshafts In Anagenmentioning
confidence: 99%
“…from the hair root.It was concluded that measurements of hair shaft diameters can be described Dy a multivariate normal distribution for an uncountably infinite number of variables.EVIDENCE is accumulating which implies that malnutrition and other illnesses effect a reduction of hair shaft diameter (Sims, 1968). The greatest diameters of the hairs were measured proximally just above the hair root and distally 40 mm.…”
mentioning
confidence: 99%
“…EVIDENCE is accumulating which implies that malnutrition and other illnesses effect a reduction of hair shaft diameter (Sims, 1968). Biophysical experiments on protein synthesis in the cortical cells of rat anagen follicles have shown that cortical cells synthesize and accumulate proteins at a very rapid rate (Sims, 1964(Sims, , 1966.…”
mentioning
confidence: 99%
See 1 more Smart Citation